The multi-pathway treatment of flavonoids as natural compounds in neurological diseases: achievements, limitations, and prospects - Fan, Yuzhu; Lian, Xiaotong; Ren, Xudong; Ren, Liqun; Liu, Cuizhe; Meng, Yanbin; Zhang, Lin (Frontiers in Neuroscience, 2025)
BackgroundThe nervous system governs fundamental life activities and higher neural functions, maintaining the body’s interaction with the external environment and internal homeostasis. Neurological diseases are a common and complex group of disorders that severely impair patients’ quality of life and physical health. Flavonoids, as a class of active components widely present in natural plants, play a crucial role in the research on neurological diseases.ObjectiveThe purpose of this review is to systematically sum up the action mechanisms, research advancements, and existing clinical uses of flavonoids in preventing and treating neurological diseases, probing into their potential in the management of neurological diseases.MethodsBy searching databases including PubMed, Web of Science, Embase, Wiley, Springer, NPG, ACS, Elsevier, and RSC, literature published between 2000 and 2025 concerning the treatment of neurological diseases with flavonoids was collected from both domestic and international sources. Priority should be given to flavonoids that have been confirmed by existing studies to be directly related to the pathogenesis or intervention effect of neurological diseases, with high quality and no contradictory results, clear chemical structures and definite metabolic pathways in vivo. Flavonoids that have no clear neurological association, have only been reported once and lack repeated verification or have a low level of evidence, and whose structures have not been resolved or whose metabolic processes are ambiguous should be excluded. After excluding studies with duplicate components and mechanisms, as well as outdated ones, a total of 190 core studies were finally screened and included from more than 15,000 literatures. These were systematically organized, categorized, and analysed across five dimensions: types of flavonoids, disease categories, experimental models, regulatory effects, and key targets.ResultsFlavonoids can exert neuroprotective effects in the prevention and treatment of neurological diseases through multiple pathways, such as anti-inflammation, anti-oxidation, anti-apoptosis, and neurotransmitter regulation.ConclusionFlavonoids exhibit clear pharmacological effects and favorable safety profiles in the prevention and treatment of neurological diseases, laying a foundation for the research and development of new drugs.